CHALEPIN AND RUTAMARIN ISOLATED FROM RUTA ANGUSTIFOLIA INHIBIT CELL GROWTH IN SELECTED CANCER CELL LINES (MCF7, MDA-MB-231, HT29, AND HCT116) - Musa Isah Fakai; Saiful Anuar Karsani; Sri Nurestri Abd Malek, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Many anticancer drugs have their origin in natural sources like plants. In this study, extracts from Ruta angustifolia were screened against four (4) selected cancer cell lines and a normal lung fibroblast cell line (MRC-5). The chloroform extract showed higher cytotoxic activity against MCF7, HT29, HCT116, but mild cytotoxicity against MDA-MB231 and no activity against MCR5 (IC50 > 100g/mL). Chalepin and rutamarin were then isolated from the active chloroform extract. Chalepin displayed remarkable cytotoxicity against all tested cancer cell lines but no activity against MCR5. Rutamarin, on the other hand, showed remarkable cytotoxicity activity against MCF7, HT29, and HCT116, whereas no activity against MDA-MB-231 and MRC5 was observed. The present study therefore revealed that chalepin and rutamarin inhibit cell growth against cancer cell lines in a dose and time-dependent manner. These initial results, therefore, suggests that chalepin and rutamarin may serve as potential source of anticancer agents.